Predicting manufacturing employee turnover intentions - Angie R. Skelton; Deborah Nattress; Rocky J. Dwyer (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - Employee turnover expenses can cost businesses more than 100 per cent of a single employee's annual wages and negatively affection an organization's production and profits. High employee turnover also could affect community tax collections, social programs and physical and mental health issues. Therefore, understanding contributors to higher employee turnover remains essential for organizational managers from both a corporate and societal standpoint. This paper aims to provide an analysis of how job satisfaction and job embeddedness could predict employee turnover intent. Design/methodology/approach - A randomly selected survey which consisted of Andrews and Withey's (1976) job satisfaction questionnaire, a global job embeddedness scale (Crossley et al., 2007) and a three-item turnover intent questionnaire derived from a survey created by Mobley et al. (1978) using a Likert-type measurement to survey randomly selected individuals used within manufacturing plants located in the Southeastern USA. Findings - The results of the multiple regression analysis showed a significant relationship between job satisfaction, job embeddedness and turnover intent; and that satisfied and committed employees are less likely to plan to leave their employment. Originality/value - Limited current information is available on how job satisfaction and job embeddedness predict turnover intentions in US Southeast manufacturing. This study includes information that shows the importance of job satisfaction and job embeddedness on retaining employees in this region and industry. Given the importance of employee retention on corporate productivity, morale and profits along with the ability to improve the organization's positive contribution to society, it is important for managers to understand these factors and their effect on employee turnover intent.
Keywords: 330; Employee retention; Employee turnover intentions; Job embeddedness; Job satisfaction; Manufacturing